PENERAPAN VIDEO INTERAKTIF ALUR MERRDEKA UNTUK MENINGKATKAN KEMAMPUAN BERNALAR KRITIS DI SMAN 10 PONTIANAK - Dede Yetty Suminar (Universitas Tanjungpura, 2022)
The results of a preliminary study conducted through interviews with teachers and assessments of students showed that there were difficulties due to learning during the COVID-19 pandemic. Learning loss occurred. Critical reasoning ability which is actually important for students, especially in physics learning is very low. One of the strategies used to overcome learning loss in critical reasoning skills is the application of the MERRDEKA learning video for Bernoulli's legal material. This Android-based interactive video compiled based on the MERRDEKA flow can be used at school or at home independently due to limited face-to-face meeting. This study is the preexperimental design method, type one group pretest-posttest. The study was conducted on 30 students of class XI IPA SMAN 10 Pontianak. The results tested using the Paired Sample T-Test showed the critical reasoning ability value of Sig (2-tailed)